Legal Protection of Minority Shareholders Through Derivative Lawsuits - Adi Widjaja (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
One of the principles known in legal science is the principle of â€œmajority rule Minority Protectionâ€, this principle emphasizes that minority shareholders are considered for their interests and rights. This is because with a minority position, they tend to be less protected rights compared to majority shareholders. The legal protection of the majority shareholders is quite guaranteed, especially through the general meeting of shareholders (RUPS). While the protection of minorities this is a new thing and get less attention. The problem in this study is the regulation of legislation against minority shareholders in closed companies in Indonesia and how the legal remedies of minority shareholders related to violations of their rights. Law No. 40 of 2007 concerning Limited Liability Companies (PT Law) has stipulated that minority shareholders who are harmed due to members of the Board of directors making mistakes or negligence may file a lawsuit against the company (direct lawsuit) and file a lawsuit on behalf of the company (derivative lawsuit). This legal research used normative juridical approach. The data used were primary and secondary data which were analyzed using quantitative method. The results showed that the concept of derivative action provides a balance between effective recovery for shareholders on the one hand and on the other hand provides flexibility to the board of directors to make decisions that are free from shareholder interference. This concept is based on the principle that shareholders should not be involved in managerial matters within the company. In addition, the concept of derivative action plays a role in corporate governance, by providing a deterrent effect against members of the company's Board of directors or commissioners who commit irregularities or fraud. The court shall conduct a stage of testing or examination of errors that have been committed previously by the company concerned, if the company or the company is proven guilty then it can be summoned to a court which will thereafter be decided or tried, in court only accept and examine the derivative lawsuit, provided that the shareholders own at least 1/10 of the shares or 10% of the total number of shares with voting rights, if the commissioners and or directors make a mistake. Then it is considered effective if as long as the regulation is good and regulates certain existing or applicable laws. However, if as long as the court or shareholders see from the law does not match the existing regulations then it is said to be ineffective.